Angelina ballerina - Holabird, Katharine; Craig, Helen (Middleton, Wis. : Pleasant Company Publications, 2000)
Angelina loves to dance and wants to become a ballerina more than anything else in the world.
"Ages 3 and up" -- Jacket
Accelerated Reader AR
Keywords: Mice -- Juvenile fiction; Ballet dancing -- Juvenile fiction; Ballerinas -- Juvenile fiction